Chromosome Engineering in Tropical Cash Crops - Bolaños Villegas, Pablo Alberto (2020)
Tropical and subtropical crops such as coffee, cacao, and papaya are valuable commodities, and their consumption is a seemingly indispensable part of the daily lives of billions of people worldwide. Conventional breeding of these crops is long, and yields are threatened by global warming. Traditional chromosome engineering and new synthetic biology methods could be used to engineer new chromosomes, facilitate the transmission of wild traits to improve resistance to stress and disease in these crops, and hopefully boost yields. This review gives an overview of these approaches. The adoption of these approaches may contribute to the resilience of agricultural communities, lead to economic growth and secure the availability of key resources for generations to come.